Legal and Constitutional Gaps in Strategic Environmental Assessment: Between Formality and Substantive Environmental Protection in Indonesia - Arifin, Firdaus; Rahayu, Mella Ismelina Farma; Maarif, Ihsanul; Susanto, Anthon F; Murbani, Anastasia Wahyu (Magister of Law, Faculty of Law, University of Mataram, 2025)
The Indonesian Strategic Environmental Assessment (SEA) is governed by Law No. 32 of 2009 on Protection and Management of the Environment. However, the implementation of Strategic Environmental Assessment still faces significant challenges, especially in fulfilling the constitutional rights of citizens to a healthy and sustainable environment. The misalignment between Strategic Environmental Assessment (SEA) practices and constitutional principles, particularly regarding transparency, public participation, and environmental justice, has contributed to violations of environmental rights and the perpetuation of social injustice in the development processes. This study aims to analyze the constitutionality of SEA’s application in the context of sustainable development in Indonesia. This study uses a normative legal method with legislative, conceptual, and comparative approaches. The research results indicate that the implementation of SEA is still inconsistent with the Constitution, particularly in protecting environmental rights. Weakness of oversight and the lack of sanctions for violations of the Environmental Impact Assessment are the main obstacles to its implementation. This study has implications for the need for reforms in law enforcement, strengthening of oversight, and increasing community participation in the SEA process to ensure environmental protection and citizens’ constitutional rights.